Adolescent Empathy Concerning Parenting Style and Peer Social Support Based on Gender Differences - Ramadhanti, Auliya; Putra, Rahman Pranovri; Fathiyah, Kartika Nur; Jannah, Ega Nurratul; Rouns, Eric (International Journal of Islamic Educational Psychology, 2024)
Empathy is crucial for individuals to interact well with others, but it has been declining among teenagers. This decline has led to increased bullying and antisocial behavior. This study aims to examine empathy in adolescents in terms of parenting, peer social support, and gender. The study involved 176 samples using a cluster random sampling technique, which included all 11th-grade students of SMA 11 Jambi City. The research follows a quantitative approach using multiple linear regression tests and independent sample T-tests to compare empathy based on gender. The results showed that authoritarian parenting affects empathy by 0.8%, democratic parenting affects empathy by 5.8%, permissive parenting affects empathy by 4.7%, peer social support significantly affects empathy by 27.9%, and overall parenting and peer social support together influence empathy by 71.9%. A comparison of empathy by gender found that women scored higher than men, with a mean difference of 1.43 and a significance of 0.005, indicating a significant difference. The novelty of this study lies in its exploration of how gender differences also impact adolescent empathy, which can help parents optimize their parenting and create a positive peer environment for adolescents in order to foster empathy within them.